Investigations into the nucleation dynamics of the stable Na-metal anode: revealing the role of a tin-infused carbon nanofiber interlayer - Wasnik, Kundan; Yadav, Poonam; Ahuja, Manuj; Mirzapure, Vinay; Johari, Priya; Shelke, Manjusha V. (ACS Applied Materials & Interfaces, 2025)
Fundamental understanding and controlling of sodium nucleation are essential for enhancing the performance, safety, and longevity of sodium metal batteries, which is not yet clearly understood in the case of sodium metal batteries. The present study showcases how a modification in the host material influences nucleation kinetics. Current-time transient studies on copper, carbon nanofiber, and tin-embedded carbon nanofiber interlayers employing the Scharifker-Hills model elucidate the mode of nucleation. This work tries to delve deep and presents a case study on how a tin-based interlayer can not only minimize the barrier for sodium nucleation but also direct the sequential progressive and instantaneous nucleation of sodium metal while reducing the overpotential substantially, resulting in crystalline, uniform Na-metal deposition. Further, to account for the complex dynamics of solid electrolyte interphase (SEI) formation distinctly associated with alkali metal deposition, the SEI-fracture model has been included, and the quantification of electrochemical nucleation parameters is obtained. The results provide important insights into the sodium nucleation mechanism, paving the way to counter dendrite formation and SEI dissolution issues of the Na-metal anode.
Keywords: overpotential; progressiveand instantaneous nucleation; Scharifker-Hills model; SEI-fracture model; tin interlayer